Physiotherapy Treatment In Cases Of Medial Part Of Left Femur Refracture E. C Metal Failure In The Orthopedic Hospital Prof. Dr. Soeharso Surakarta - Nafarin, Muhammad Febry; , Sugiono S.Fis.MH.Kes (2015)
Background: Fracture is a break bone structural continuity. Metal failure is the breaking of a plate and screw fixation of bone that occurs refracture (broken back) in areas that have experienced a fracture, one of the causes of failure of metal is strong pressure that occurs in the fracture network while doing exercises. Refrakture the left medial femoral e, c metal failure is a break a bone continuity both times in the middle part of the left femur. Signs and symptoms of a fracture in the form of deformity, swelling, bruissing (ecchymosis), muscle spasms, pain, loss of function, abnormal mobility (crepitus), and neurovascular changes. Physiotherapy exercises in the case of the femur refracture can reduce pain, edema, and can increase the area of motion and muscle strength. Objective: To know the benefits of exercise therapy in the form of: a) useful in reducing static contraction and decrease edema so the pain will be reduced, b) active motion exercises beneficial in maintaining a broad range of motion, c) passive motion exercises beneficial in preventing the occurrence of limitation of motion and maintain extensive motion joints, d) active assisted movement can maintain joint function and muscle strength after a fracture, e) the exercise of force and hold-relax passive movement beneficial in improving range of motion, f) active resisted useful exercise to improve muscle strength, g) the exercise by using crutches useful in improving functional ability roads. Results: For pain with VAS: tenderness T1: 4.5 to T6: 2.5 and T1: 6.5 becomes T6: 4.5. To edema anthropometric measurements at measuring point of the patella: T1: 43 cm and T6: 41 cm, 10 cm and then down T1: 35 cm and T6: 32, then 20 cm down T1: 31 cm and T6: 31 cm, while for the measurement of ankle using 8 to obtain results T1: 50 cm and T6: 46 cm there is a decrease in edema. For muscle strength with MMT: flexor muscle T1: 3 - T6: 4 and extensor T1: -3 - T6: +3. Uutuk LGS: active knee T1: S 0- 40-80 into T6: S 0-25-95, passive knee T1: S 0-20-85 become T6: 0-5-100. Conclusion: Management of physiotherapy on condition refracture femure with exercise therapy used showed a decrease in pain, edema, increased LGS, and muscle strength.